I will plant you a lilac tree a memoir of a Schindler's list survivor - Hillman, Laura (The exchange, 2005)
In 1942 Hannelore Wolff made a difficult decision, one that changed her life forever. She left the comfort and safety of her boarding school in Berlin, Germany, and volunteered to be sent to a Polish ghetto. The Gestapo had already killed her father and were deporting her mother and brothers. Hannelore could not bear to be separated from what was left of her family so she chose to go with them. It was the beginning of her long journey through what turned out to be eight concentration camps, including Auschwitz. In one of the camps, Hannelore fell in love with a young man named Dick Hillman. After a few months they were separated, but Dick told Hannelore, "I will find you, wherever you are." He kept his promise. They were both put on Oskar Schindler's famous list and married when they were reunited. I Will Plant You a Lilac Tree is one woman's incredible story of finding courage, strength, and love during one of the most horrific times of the modern era.